2011
DOI: 10.1161/circresaha.111.245589
|View full text |Cite
|
Sign up to set email alerts
|

Signaling During Epicardium and Coronary Vessel Development

Abstract: Abstract:The epicardium, the tissue layer covering the cardiac muscle (myocardium), develops from the proepicardium, a mass of coelomic progenitors located at the venous pole of the embryonic heart. Proepicardium cells attach to and spread over the myocardium to form the primitive epicardial epithelium. The epicardium subsequently undergoes an epithelial-to-mesenchymal transition to give rise to a population of epicardiumderived cells, which in turn invade the heart and progressively differentiate into various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
99
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(106 citation statements)
references
References 146 publications
3
99
0
1
Order By: Relevance
“…Orthotopic grafting of quail proepicardial tissues into chick embryos revealed that QCPNnegative SMCs in the septal branch, as well as in arteries in the free wall, are predominantly of proepicardial origin (Supplementary Fig. S13), as reported previously [11][12][13] .…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Orthotopic grafting of quail proepicardial tissues into chick embryos revealed that QCPNnegative SMCs in the septal branch, as well as in arteries in the free wall, are predominantly of proepicardial origin (Supplementary Fig. S13), as reported previously [11][12][13] .…”
Section: Resultssupporting
confidence: 81%
“…Coronary arteries are generally accepted to form by ingrowth of angiogenic precursors into the aorta [8][9][10] , with the integration of migrating proepicardial mesenchyme as the main source of smooth muscle cells (SMCs) [11][12][13] . On the other hand, quail-chick chimera experiments have shown that the cardiac NC does not differentiate into coronary SMCs, although ganglia of NC origin are associated with the proximal portion of coronary arteries 10,14 .…”
mentioning
confidence: 99%
“…To understand the morphogenesis of the coronary vascular system fully, we need to uncover the molecular and cellular mechanisms that integrate different endothelial compartments (i.e., the embryonic arterial and venous coronary vasculature) into a single, continuous vascular bed and to identify the origin of coronary endothelial progenitors (1). In this regard, Katz and collaborators (13) have proven that the PE comprises several cell compartments (identified by either Scleraxis or Semaphorin3D gene expression) that contribute differentially to CoE.…”
Section: Discussionmentioning
confidence: 99%
“…G2-Gata4-driven reporter expression first is confined to the epicardium and its mesenchymal derivatives (1,(20)(21)(22) and then expands to the CoE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation